Case Report: A case of primary pericardial mesothelioma treated with multimodal combined therapy - Gong, Jinlan; Wu, Xiaofeng; Wang, Jiehua (Frontiers in Cardiovascular Medicine, 2024)
Primary pericardial mesothelioma (PMPM) is a rare, aggressive, and lethal form of cancer. It arises from pericardial mesothelial cells, with an incidence of less than 0.002%. Various risk factors contribute to this disease, such as asbestos exposure, viral infections, radiation exposure, immunodeficiency, and genetics. Clinical signs include constrictive pericarditis, pericardial effusion, and heart failure. Diagnosis relies on histopathological examination. PMPM is clinically rare with a poor prognosis, typically resulting in an average median survival time of 6-10 months. Currently, treatment lacks prospective evidence and specific clinical recommendations, relying on treatment experience documented in case reports. This report presents a case of PMPM in an adult female with atypical symptoms and explores the potential of multimodal combined therapy as a new treatment option.A 62-year-old female patient presented to our department in September 2023. The patient complained that she suffered from chest pain, right upper limb swelling and fatigue about one week. She was in the state of anxiety and depression for the last 8 years. She was a smoker consuming 1 pack of cigarettes every 4 days. She had no history of occupational asbestos exposure.A comprehensive medical history was conducted. In May 2023, the patient sought care at our hospital's fever clinic due to " lower fever and dry cough." Initially, a "respiratory tract infection" was suspected, and chest CT scan was performed and revealed irregular thickened pericardium (Fig. 1).